Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Experimental Challenge of Chinook Salmon ( Oncorhynchus tshawytscha ) With Tenacibaculum maritimum and Tenacibaculum dicentrarchi Fulfils Koch's Postulates - Karthiga Kumanan; Jeremy Carson; Ryan B. J. Hunter; Anne Rolton; Ulla von Ammon; Chaya Bandaranayake; Connie Angelucci; Richard N. Morrison; Seumas P. Walker; Jane E. Symonds; Kate S. Hutson (Journal of Fish Diseases, 2025)
The bacterial skin disease tenacibaculosis, caused by Tenacibaculum species, affects numerous economically important marine fish, including salmonids. This study reports the ability of three Tenacibaculum maritimum strains, belonging to different molecular O‐AGC types, and a single Tenacibaculum dicentrarchi strain to induce tenacibaculosis in farmed Chinook salmon ( Oncorhynchus tshawytscha , Walbaum 1792) in Aotearoa New Zealand. Naïve Chinook salmon were exposed to T. maritimum (2 × 10 8 cells/mL) and T. dicentrarchi (2 × 10 7 cells/mL) by immersion using natural seawater. Clinical signs of tenacibaculosis were apparent in all T. maritimum strains used in the challenged fish. Of these, 100% of the fish challenged with O‐AGC Type 2‐1 and Type 3‐2 strains became moribund, whereas only 60% of the O‐AGC Type 3‐0 challenged fish became moribund. Fish exposed to T. dicentrarchi showed more severe symptoms, exposing musculature in 51% of the challenged population, with 28% of fish becoming moribund. Gross pathological signs of fin rot, scale loss, skin ulcers and haemorrhagic skin spots were observed for both Tenacibaculum species and were consistent with those observed on farmed fish. Pure T. maritimum and T. dicentrarchi cultures were reisolated from epidermal damage of challenged fish. Tenacibaculum species was not isolated from the anterior kidney of affected fish, which indicates no systemic infection in Chinook salmon.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Optimising Outbreak Investigation, Surveillance and Discovery of Pathogens in Aquaculture Using Unbiased Metatranscriptomics - Vincenzo A. Costa; Richard J. Whittington; Charles Caraguel; Joy A. Becker; Kerrie E. Wiley; Christine Huynh; Jeremy Carson; Francisca Samsing (Reviews in Aquaculture, 2025)
Emerging infectious diseases are a major threat to global aquaculture production and are projected to increase in frequency due to anthropogenic stressors and climate change. Our ability to screen the global aquatic ‘infectome’ is dramatically improving through unbiased metatranscriptomic (i.e., total RNA) sequencing. Despite recent advances in molecular diagnostics and next‐generation sequencing, outbreak investigation in aquaculture often encounters limitations due to the targeted nature of conventional techniques, which may only capture a small portion of the diverse array of disease‐causing agents present in nature, sometimes requiring years to resolve. Here, we propose that unbiased metatranscriptomic sequencing serves as a cost‐effective and powerful technique for characterising pathogens during disease outbreaks and in surveillance programmes. In doing so, we offer a diagnostic framework to mitigate infectious disease threats to global aquaculture. We emphasise the importance of combining rapid metatranscriptomics with traditional techniques for a holistic examination of the causes of unknown aetiologies in aquatic animals, and how it can be used to examine host responses in parallel with pathogen discovery. We suggest that the integration of metatranscriptomics into aquaculture will require upskilling, proficiency testing, user‐friendly bioinformatic tools and open data sharing. Furthermore, it is essential to establish a reporting framework—with analytical guidelines—that ensures the protection of animal industries while safeguarding trade interests.

Turbidity and temperature effects on growth and gene transcription of threatened juvenile Longfin Smelt (Spirinchus thaleichthys) - Felix Biefel; Christina Pasparakis; Dennis E. Cocherell; Tien-Chieh Hung; Evan W. Carson; Nann A. Fangue; Juergen P. Geist; Anne E. Todgham; Richard E. Connon (Aquaculture, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Quantitative metrics commonly derived from diffusion tractography covary with streamline length: a characterization and method of adjustment - Richard G. Carson; Alexander Leemans (Brain Structure and Function, 2024)
Tractography algorithms are used extensively to delineate white matter structures, by operating on the voxel-wise information generated through the application of diffusion tensor imaging (DTI) or other models to diffusion weighted (DW) magnetic resonance imaging (MRI) data. Through statistical modelling, we demonstrate that these methods commonly yield substantial and systematic associations between streamline length and several tractography derived quantitative metrics, such as fractional anisotropy (FA). These associations may be described as piecewise linear. For streamlines shorter than an inflection point (determined for a group of tracts delineated for each individual brain), estimates of FA exhibit a positive linear relation with streamline length. For streamlines longer than the point of inflection, the association is weaker, with the slope of the relationship between streamline length and FA differing only marginally from zero. As the association is most pronounced for a range of streamline lengths encountered typically in DW imaging of the human brain (less than ~ 100 mm), our results suggest that some quantitative metrics derived from diffusion tractography have the potential to mislead, if variations in streamline length are not considered. A method is described, whereby an Akaike information weighted average of linear, Blackman and piecewise linear model predictions, may be used to compensate effectively for the association of FA (and other quantitative metrics) with streamline length, across the entire range of streamline lengths present in each specimen.

Understanding and valuing human connections to deep-sea methane seeps off Costa Rica - Olívia S. Pereira; Mark Jacobsen; Richard Carson; Jorge Cortés; Lisa A. Levin (Ecological Economics, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Serological and molecular typing of Tenacibaculum maritimum from New Zealand farmed salmon, Oncorhynchus tshawytscha - Karthiga Kumanan; Lizenn Delisle; Connie Angelucci; Ryan B.J. Hunter; Oleksandra Rudenko; Jeremy Carson; Richard N. Morrison; Andrew C. Barnes; Kate S. Hutson (Aquaculture, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Cold temperature stress and damaged skin induced high mortality in barramundi ( Lates calcarifer ) challenged with Vibrio harveyi - Francisca Samsing; William Zhang; Ruth N. Zadoks; Richard Whittington; Carola Venturini; Carla Giles; Jeremy Carson; Joy A. Becker (Journal of Fish Diseases, 2023)
Most diseases in aquaculture are caused by opportunistic pathogens. One of them, Vibrio harveyi , is a widespread Gram‐negative bacterium that has become an important pathogen of aquatic species in marine environments. Here, we propose the use of the causal pie model as a framework to conceptualize the causation of vibriosis in juvenile barramundi ( Lates calcarifer ) and to establish an effective challenge model. In the model, a sufficient cause, or the causal pie, is a constellation of component causes that lead to an outcome (e.g. vibriosis). In the pilot study, a high cumulative mortality (63.3% ± 10.0%, mean ± SE) was observed when V. harveyi was administered by intraperitoneal injection using a high challenge dose [10 7 colony‐forming units (CFU) fish −1 ], but low or no mortality was observed in fish subject to cold stress or fish with intact skin when challenged by immersion. We, therefore, tested the use of a skin lesion (induced with a 4‐mm biopsy punch) combined with cold temperature stress to induce vibriosis following the causal pie model. After challenge, fish were immediately subject to cold stress (22°C) or placed at an optimal temperature of 30°C. All groups were challenged with 10 8 CFU mL −1 for 60 min. A considerably higher mortality level (72.7% ± 13.9%) was observed in fish challenged with both a skin lesion and cold stress compared with mortality in fish only having a skin lesion (14.6% ± 2.8%). V. harveyi was re‐isolated from all moribund fish and was detected by species‐specific real‐time PCR in gills, head kidney and liver, regardless of challenge treatment confirming vibriosis as the cause of disease. Parenchymal tissues had histopathological changes consistent with vibriosis. Whole‐genome sequence (WGS) is provided for the Vibrio harveyi isolate examined in this study. Overall, the causal pie model was a useful framework to conceptualize the design of the experimental challenge model, in which both cold stress and skin damage were identified as component causes of vibriosis with high mortality. This conceptual framework can be applied to other opportunistic pathogens in aquaculture or to the study of co‐infections in fish.

Multiple and contrasting pressures determine intraspecific phytochemical variation in a tropical shrub - Andrea E. Glassmire; Walter P. Carson; Angela M. Smilanich; Lora A. Richards; Christopher S. Jeffrey; Craig D. Dodson; Casey S. Philbin; Garcia L. Humberto; Lee A. Dyer (Oecologia, 2023)

Genetic and genomic analyses of resistance to yersiniosis in Atlantic salmon (Salmo salar) assessed by tank challenge - Richard S. Taylor; Roberto Carvalheiro; Amanda L. Patchett; Klara L. Verbyla; Jeremy Carson; James W. Wynne; Brad S. Evans; Curtis E. Lind; Harry King (Aquaculture, 2023)

Serotonin transporter availability in physically aggressive personality disordered patients: associations with trait and state aggression, and response to fluoxetine - Daniel R. Rosell; Mark Slifstein; Judy Thompson; Xiaoyan Xu; M. Mercedes Perez-Rodriguez; Margaret M. McClure; Erin A. Hazlett; Antonia S. New; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; Larry S. Siever; et al. (Psychopharmacology, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

A Bayesian approach to analysing cortico-cortical associative stimulation induced increases in the excitability of corticospinal projections in humans - Richard G. Carson; Antonio Capozio; Emmet McNickle; Alexander T. Sack (Experimental Brain Research, 2021)
Repeated pairing of transcranial magnetic stimulation (TMS) over left and right primary motor cortex (M1), at intensities sufficient to generate descending volleys, produces sustained increases in corticospinal excitability. In other paired associative stimulation (PAS) protocols, in which peripheral afferent stimulation is the first element, changes in corticospinal excitability achieved when the second stimulus consists of brief bursts of transcranial alternating current stimulation (tACS), are comparable to those obtained if TMS is used instead (McNickle and Carson 2015). The present aim was to determine whether associative effects are induced when the first stimulus of a cortico-cortical pair is tACS, or alternatively subthreshold TMS. Bursts of tACS (500 ms; 140 Hz; 1 mA) were associated (180 stimulus pairs) with single magnetic stimuli (120% resting motor threshold rMT) delivered over the opposite (left) M1. The tACS ended 6 ms prior to the TMS. In a separate condition, TMS (55% rMT) was delivered to right M1 6 ms before (120% rMT) TMS was applied over left M1. In a sham condition, TMS (120% rMT) was delivered to left M1 only. The limitations of null hypothesis significance testing are well documented. We therefore employed Bayes factors to assess evidence in support of experimental hypotheses—defined precisely in terms of predicted effect sizes, that these two novel variants of PAS increase corticospinal excitability. Although both interventions induced sustained (~ 20–30 min) increases in corticospinal excitability, the evidence in support of the experimental hypotheses (over specified alternatives) was generally greater for the paired TMS-TMS than the tACS-TMS conditions.

Seawater transmission and infection dynamics of pilchard orthomyxovirus (POMV) in Atlantic salmon ( Salmo salar ) - Francisca Samsing; Megan Rigby; Hedda K. Tengesdal; Richard S. Taylor; Daniela Farias; Richard N. Morrison; Scott Godwin; Carla Giles; Jeremy Carson; Chloe J. English; Roger Chong; James W. Wynne (Journal of Fish Diseases, 2021)
The Tasmanian salmon industry had remained relatively free of major viral diseases until the emergence of pilchard orthomyxovirus (POMV). Originally isolated from wild pilchards, POMV is of concern to the industry as it can cause high mortality in farmed salmon ( Salmo salar ). Field observations suggest the virus can spread from pen to pen and between farms, but evidence of passive transmission in sea water was unclear. Our aim was to establish whether direct contact between infected and naïve fish was required for transmission, and to examine viral infection dynamics. Atlantic salmon post‐smolts were challenged with POMV by either direct exposure via cohabitation or indirect exposure via virus‐contaminated sea water. POMV was transmissible in sea water and direct contact between fish was not required for infection. Head kidney and heart presented the highest viral loads in early stages of infection. POMV survivors presented low viral loads in most tissues, but these remained relatively high in gills. A consistent feature was the infiltration of viral‐infected melanomacrophages in different tissues, suggesting an important role of these in the immune response to POMV. Understanding POMV transmission and host–pathogen interactions is key for the development of improved surveillance tools, transmission models and ultimately for disease prevention.

The rate of dasotraline brain entry is slow following intravenous administration - Robert Lew; Cristian C. Constantinescu; Daniel Holden; Richard E. Carson; Vincent Carroll; Gerald Galluppi; Kenneth S. Koblan; Seth C. Hopkins (Psychopharmacology, 2020)
Rationale Drugs that rapidly increase dopamine levels have an increased risk of abuse. Dasotraline (DAS) is a dopamine and norepinephrine reuptake inhibitor characterized by slow oral absorption with low potential for abuse. However, it remains unclear whether intravenous (i.v.) administration would facilitate the rapid elevation of dopamine levels associated with stimulant drugs. Objective To assess the kinetics of DAS across the blood-brain barrier and time to onset of dopamine transporters (DAT) inhibition. Methods We compared the onset of DAT occupancy and the associated elevation of synaptic dopamine levels in rhesus monkey following i.v. administration of DAS or methylphenidate (MPH) using positron emission tomography (PET). Brain entry times were estimated by reductions in [ 18 F]-FE-PE2I binding to DAT in rhesus monkeys. Elevations of synaptic dopamine were estimated by reductions in [ 11 C]-Raclopride binding to D 2 receptors. Results Intravenous administration of DAS (0.1 and 0.2 mg/kg) resulted in striatal DAT occupancies of 54% and 68%, respectively; i.v. administered MPH (0.1 and 0.5 mg/kg) achieved occupancies of 69% and 88% respectively. Brain entry times of DAS (22 and 15 min, respectively) were longer than for MPH (3 and 2 min). Elevations in synaptic dopamine were similar for both DAS and MPH however the time for half-maximal displacement by MPH ( t = 23 min) was 4-fold more rapid than for DAS ( t = 88 min). Conclusions These results demonstrate that the pharmacodynamics effects of DAS on DAT occupancy and synaptic dopamine levels are more gradual in onset than those of MPH even with i.v. administration that is favored by recreational drug abusers.

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Transcallosal connectivity of the human cortical motor network - Kathy L. Ruddy; Alexander Leemans; Richard G. Carson (Brain Structure and Function, 2017)

Preferential binding to dopamine D3 over D2 receptors by cariprazine in patients with schizophrenia using PET with the D3/D2 receptor ligand [11C]-(+)-PHNO - Ragy R. Girgis; Mark Slifstein; Deepak D’Souza; Yih Lee; Antonia Periclou; Parviz Ghahramani; István Laszlovszky; Suresh Durgam; Nika Adham; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; et al. (Psychopharmacology, 2016)
Rationale Second-generation antipsychotics occupy dopamine D 2 receptors and act as antagonists or partial agonists at these receptors. While these drugs alleviate positive symptoms in patients with schizophrenia, they are less effective for treating cognitive deficits and negative symptoms. Dopamine D 3 receptors are highly expressed in areas of the brain thought to play a role in the regulation of motivation and reward-related behavior. Consequently, the dopamine D 3 receptor has become a target for treating negative symptoms in combination with D 2 antagonism to treat positive symptoms in patients with schizophrenia. Objective The purpose of this study was to determine the cariprazine receptor occupancies in brain for D 2 and D 3 receptors in patients with schizophrenia. Methods Using [ 11 C]-(+)-PHNO as a radioligand, positron emission tomography (PET) scans were performed in eight patients at baseline and postdose on days 1, 4, and 15. Plasma and cerebrospinal fluid (CSF) samples were analyzed for cariprazine concentrations. Results A monotonic dose-occupancy relationship was observed for both receptor types. After 2 weeks of treatment, near complete (∼100 %) occupancies were observed for both receptors at a dose of 12 mg/day. At the lowest cariprazine dose (1 mg/day), mean D 3 and D 2 receptor occupancies were 76 and 45 %, respectively, suggesting selectivity for D 3 over D 2 receptors at low doses. An exposure-response analysis found a ∼3-fold difference in EC 50 (D 3 = 3.84 nM and D 2 = 13.03 nM) in plasma after 2 weeks of dosing. Conclusion This PET imaging study in patients with schizophrenia demonstrated that cariprazine is a D 3 -preferring dual D 3 /D 2 receptor partial agonist.

Training-induced modifications of corticospinal reactivity in severely affected stroke survivors - Ruth N. Barker; Sandra G. Brauer; Benjamin K. Barry; Toby J. Gill; Richard G. Carson (Experimental Brain Research, 2012)

Visual target separation determines the extent of generalisation between opposing visuomotor rotations - Daniel G. Woolley; Aymar de Rugy; Richard G. Carson; Stephan Riek (Experimental Brain Research, 2011)

Real-time error detection but not error correction drives automatic visuomotor adaptation - Mark R. Hinder; Stephan Riek; James R. Tresilian; Aymar de Rugy; Richard G. Carson (Experimental Brain Research, 2010)

Training-induced changes in the pattern of triceps to biceps activation during reaching tasks after chronic and severe stroke - Ruth Nancy Barker; Sandra Brauer; Richard Carson (Experimental Brain Research, 2009)

Common input to different regions of biceps brachii long head - Benjamin K. Barry; Michael A. Pascoe; Stephan Riek; Richard G. Carson; Roger M. Enoka (Experimental Brain Research, 2009)

The efficacy of colour cues in facilitating adaptation to opposing visuomotor rotations - Mark R. Hinder; Daniel G. Woolley; James R. Tresilian; Stephan Riek; Richard G. Carson (Experimental Brain Research, 2008)

Neuromuscular and biomechanical factors codetermine the solution to motor redundancy in rhythmic multijoint arm movement - Aymar de Rugy; Stephan Riek; Yalchin Oytam; Timothy J. Carroll; Rahman Davoodi; Richard G. Carson (Experimental Brain Research, 2008)

The interference effects of non-rotated versus counter-rotated trials in visuomotor adaptation - Mark R. Hinder; Laura Walk; Daniel G. Woolley; Stephan Riek; Richard G. Carson (Experimental Brain Research, 2007)

Dual adaptation to two opposing visuomotor rotations when each is associated with different regions of workspace - Daniel G. Woolley; James R. Tresilian; Richard G. Carson; Stephan Riek (Experimental Brain Research, 2007)

Influence of predominant patterns of coordination on the exploitation of interaction torques in a two-joint rhythmic arm movement - Aymar de Rugy; Stephan Riek; Richard G. Carson (Experimental Brain Research, 2006)

Neuromuscular-skeletal constraints on the acquisition of skill in a discrete torque production task - Jonathan Shemmell; Matthew Forner; Benjamin Tathem; James R. Tresilian; Stephan Riek; Benjamin K. Barry; Richard G. Carson (Experimental Brain Research, 2006)

Intramuscular aripiprazole for the treatment of acute agitation in patients with schizophrenia or schizoaffective disorder: a double-blind, placebo-controlled comparison with intramuscular haloperidol - Raisa Andrezina; Richard C. Josiassen; Ronald N. Marcus; Dan A. Oren; George Manos; Elyse Stock; William H. Carson; Taro Iwamoto (Psychopharmacology, 2006)

Age-related differences in rapid muscle activation after rate of force development training of the elbow flexors - Benjamin K. Barry; Geoffrey E. Warman; Richard G. Carson (Experimental Brain Research, 2005)

Transfer of resistance training to enhance rapid coordinated force production by older adults - Benjamin K. Barry; Richard G. Carson (Experimental Brain Research, 2004)

Bimanual coordination: constraints imposed by the relative timing of homologous muscle activation - Yong Li; Oron Levin; Richard G. Carson; Stephan P. Swinnen (Experimental Brain Research, 2004)

Flooding in the Red River Basin – Lessons from Post Flood Activities - Slobodan P. Simonovic; Richard W. Carson (Natural Hazards, 2003)

The effect of obstacle position on reach-to-grasp movements - Vanessa L. Coppard; James R. Tresilian; Mark Mon-Williams; Richard G. Carson (Experimental Brain Research, 2001)

Let your feet do the walking: constraints on the stability of bipedal coordination - Stephan Riek; Richard G. Carson (Experimental Brain Research, 2001)

Patterns of woody plant abundance, recruitment, mortality, and growth in a 65 year chronosequence of old-fields - Dan Lawson; Richard S. Inouye; Nancy Huntly; Walter P. Carson (Plant Ecology, 1999)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)